Mitoferrin2 is a synthetic lethal target for chromosome 8p deleted cancers - Krieg, Stephan; Rohde, Thomas; Rausch, Tobias; Butthof, Luise; Wendler-Link, Lena; Eckert, Christoph; Breuhahn, Kai; Galy, Bruno; Korbel, Jan Oliver; Billmann, Maximilian; Breinig, Marco; Tschaharganeh, Darjus-Felix (Genome medicine, 2024)
Background: Somatic copy number alterations are a hallmark of cancer that offer unique opportunities for therapeutic exploitation. Here, we focused on the identification of specific vulnerabilities for tumors harboring chromosome 8p deletions. Methods: We developed and applied an integrative analysis of The Cancer Genome Atlas (TCGA), the Cancer Dependency Map (DepMap), and the Cancer Cell Line Encyclopedia to identify chromosome 8p-specific vulnerabilities. We employ orthogonal gene targeting strategies, both in vitro and in vivo, including short hairpin RNA-mediated gene knockdown and CRISPR/Cas9-mediated gene knockout to validate vulnerabilities. Results: We identified SLC25A28 (also known as MFRN2), as a specific vulnerability for tumors harboring chromosome 8p deletions. We demonstrate that vulnerability towards MFRN2 loss is dictated by the expression of its paralog, SLC25A37 (also known as MFRN1), which resides on chromosome 8p. In line with their function as mitochondrial iron transporters, MFRN1/2 paralog protein deficiency profoundly impaired mitochondrial respiration, induced global depletion of iron-sulfur cluster proteins, and resulted in DNA-damage and cell death. MFRN2 depletion in MFRN1-deficient tumors led to impaired growth and even tumor eradication in preclinical mouse xenograft experiments, highlighting its therapeutic potential. Conclusions: Our data reveal MFRN2 as a therapeutic target of chromosome 8p deleted cancers and nominate MFNR1 as the complimentary biomarker for MFRN2-directed therapies.
Gesehen am 25.11.2024